ORGANIC SUBSTANCES ABSORPTION OF CORAL BACTERIAL COMMUNITY IN CAT BA - LONG CHAU ISLAND AREAS - Thu, Pham The; Betteral, Yvan; Ha, Bui Thi Viet; Ngai, Nguyen Dang (Vietnam Journal of Marine Science and Technology, 2014)
Coral provide habitat and nutrient source for bacteria, but bacteria also play an important role in nutrition, metabolism and health of coral. Therefore understand the relationships and roles between them will play an important role in the recovery, ensure coral productivity and the coral health. In which there is functional variation of the coral bacterial community or not should also be investigated. Therefore, to contribute to clarify these issues, the function of bacterial communities on corals has to be investigated, and ecological experiment of Biolog EcoPlate on the absorption and metabolism of 31 organic compounds belonging to 06 substrate groups (carbohydrates, amino-acids, phenols, carboxylic acids, polymers and amines) of bacterial community living on 09 coral species and the surrounding waters in Long Chau and Cat Ba Island (Hai Phong) has been carried out. Research results showed that, the bacterial community have capable absorption all 31 organic substances, the ability to reduce volatility from coral mucus to the environmental water around, from the environmental water around coral in Cat Ba to Long Chau and from coral mucus at Long Chau to Cat Ba except the group of amines, and the multivariate correlation between the absorption function of organic of bacterial community with the environmental factors.